Work in the interests of rail transport: the second Minister of Railway Transport of the Russian Empire – Volodymyr O. Bobrynskyi (1869-1871) - Oleh Pylypchuk; Oleh Strelko (History of science and technology, 2019)
The expanded and comprehensive study of the way of life of the personalities of prominent figures who have made a significant contribution to the formation and development of homeland and world science remains a topical task of historical science at the present stage of its development. The article is devoted to the coverage and periodization of stages of life and activities in the field of railroad construction of the Russian Empire, of its second Minister of Railway Transport Volodymyr O. Bobrynskyi. The preconditions of V. O. Bobrynskyi’s career growth have been considered. The article shows how the study at St. Petersburg University influenced the formation of V. O. Bobrynskyi’s personality. The stages of the military career of V. O. Bobrynskyi during the Crimean War of 1854-1856 have been investigated. Analysis of V. O. Bobrynskyi’s activity in different public positions until he was appointed as the Minister of Railway Transport, allowed to assess his contribution to state building and the development of the Russian Empire in various fields. It has been established that Volodymyr Bobrynskyi, acting as the Minister of Railway Transport of the Russian Empire, became the initiator of the construction of 27 railway lines, and as the creator of the network of railways, including the Ukrainian segment. His activities during the administration of the ministry were aimed at strategic directions for the development of railways, in particular: to establish links between the railways that were still divided; to ensure continuation of lines that were not adjacent to the general railway network; to connect internal provinces with seaports (with Mykolaiv and Mariupol); to develop the railways in the interests of the coal and mining industry, as well as the Vologda and Vyatka-Dvina lines. In addition, on the initiative of the Minister, it was envisaged to include two strategic railway lines - from Prague to Warsaw and from Lukov to Ivanogorod. Analysis of reforms of V. O. Bobrynskyi in the management of the railways ...